Advertising at War - INGER L. STOLE (University of Illinois Press, 2012)
The past two decades have witnessed an increased interest in advertising and consumer issues across scholarly disciplines. Fields ranging from business and advertising to sociology, American studies, history, mass communication, art history, anthropology, and psychology are recognizing the centrality of consumption and consumer-related issues to their scholarly pursuits. Most scholars explore these issues from contemporary perspectives, although the recent appearance of historical accounts suggests the emergence of additional approaches.1 To date, however, the historical approach has favored the decades flanking World War II, leaving advertising and consumer issues that emerged in connection with war conditions largely undocumented.2 Thus, scholars have yet to provide a comprehensive account of the advertising industry’s behavior in the larger social, economic, and political context of the war or to explore the significance of these events for helping advertising to become an inviolable American institution in the postwar era. Advertising at War: Business, Consumers, and Government in the 1940s therefore casts a wider net, mapping the ongoing tensions between advertisers, regulators, and consumer activists during the war and chronicling how advertisers turned a situation that by all rational accounts should have worked to their disadvantage into a priceless opportunity to cement their place in a postwar society defined by advertising and the consumer products it promoted. Advertising achieved this status between 1942 and 1945, economically at first, and then politically and culturally. A successful campaign to achieve favorable laws and regulations eliminated any realistic threat to the institution’s role in the economic system